Eco-epidemiology of prey and competitive predator species in the SEI model - R. Sivakumar; S. Vijaya (The Scientific Temper, 2024)
The ecological epidemiology structure explores the relationship between disease and competitiveness in a predator-prey [22] (Vijaya S, J. J, 2017) structure. We create a mathematical model that includes a susceptible (S), exposed (E), and infected (I)[28][22] (Vijaya S, J.J, 2017)( S.P.Bera, A. M, 2015) subpopulation of prey, as well as a competing predator. The model Examines how disease transmission, predation rates, and natural population dynamics affect structure stability. The findings provide insights into illness prevalence and population levels, which could help researchers better understand disease outbreaks and the function of predators in disease control. Further studies should examine spatial aspects, environmental consequences, and predator behaviors.